2014
DOI: 10.1186/1472-6831-14-99
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation in 5071 southern Taiwanese patients with potentially malignant oral mucosal disorders

Abstract: BackgroundOral cancers can be preceded by clinically evident oral potentially malignant disorders (OPMDs). The current study evaluated the rate and the time of malignant transformation in the various OPMDs in a cohort of patients from southern Taiwan. Parameters possibly indicative for malignant transformation of OPMDs, such as epidemiological and etiological factors, and clinical and histopathological features were also described.MethodsWe followed-up 5071 patients with OPMDs—epithelial dysplasia with oral su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
131
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 30 publications
10
131
3
6
Order By: Relevance
“…Previous studies have reported that men underwent malignant transformation more frequently than women [15,16]. In the present study, the expansion of lesion and malignant transformation were more frequent in men than in women.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Previous studies have reported that men underwent malignant transformation more frequently than women [15,16]. In the present study, the expansion of lesion and malignant transformation were more frequent in men than in women.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have evaluated the clinicopathological factors predictive of malignant transformation in patients with oral leukoplakia and demonstrated significant differences in age, gender, cite of lesion, size of lesion, number of sites affected, and clinical and pathological appearance of the lesions [12][13][14][15][16][17][18][19]. In the present study, the lesions that were non-homogenous and located on the tongue presented with a higher grade were likely to progress into cancer.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…On the other hand, 18 cases in the OPMD II group showed malignant transformation to OSCC within 1.2-65.5 mo; these cases included 1 each of erythroleukoplakia, erythroplakia plus submucous fibrosis, submucous fibrosis, and speckle leukoplakia, 4 cases of verrucous hyperplasia, and 10 cases of verrucous hyperplasia plus submucous fibrosis. In this cohort, the malignant transformation rate of the OPMD II patients was about 20.5% (18/88), which was twofold higher than that among the OPMD patients (11.8%, 18/153) (18)(19)(20). The clinical characteristics and follow-up data of the 88 OPMD II cases are detailed in SI Appendix, Table S10.…”
Section: Quantification Of Salivary Proteins By Multiplex Lc-mrm-msmentioning
confidence: 91%
“…3,5,8,9,18,21 Não há dúvidas de que o CCE representa 90% dos cânceres de boca, tendo em vista sua alta incidência em nosso meio, caracterizando-o como a neoplasia maligna mais comum na cavidade oral. 2,4,[12][13][14][15][16]19,20 3 Parlatescu et al, 4 Patrício 5 e Rodrigues et al 6 concordam que se trata da lesão pré maligna mais comum. Torras et al, 2 Parlatescu et al, 4 Patrício, 5 Neville et al 10 e Abidullah et al 21 justificam sua significância ao afirmarem que CCEs orais vêm sendo associados ou precedidos de lesões pré-malignas, com destaque para a LO.…”
Section: Discussionunclassified